Future prospective of nanophytovirology: A review - Anupriya (International Journal of Pharmacy with Medical Sciences, 2024)
Plant viral diseases are threating for sustainable agriculture and cause financial ruin for formers. In recent scenario advanced nanoparticles are the best tool for the management of plant viral diseases in the field of for agronomy. The application of nanotechnology for management of plant viral disease are called nanophytovirology. These nanoparticles are managing plant diseases by variety of ways like directly inhibiting viral replication, antiviral drug delivery agent, increase the viral disease resistance of plants and deactivating viruses. In this way nanoparticles offer a versatile approach for controlling viral infections, from early detection to treatment and prevention. Through antiviral assays researchers proves that different nanoparticles have shown excellent virucidal properties against various plant viruses. The present review discusses about a new field of nanophytovirology which focusing on the use of nanotechnology to manage not only detection of plant viral diseases but also its control.